Forsaking all others [videorecording (DVD)] - Van Dyke, W. S.; Crawford, Joan, 1908-1977; Gable, Clark, 1901-1960; Montgomery, Robert, 1904-1981; Butterworth, Charles, 1896-1946; Burke, Billie, 1885-1970; Russell, Rosalind; Treacher, Arthur, 1894-1975; Roberts, Edward Barry; Cavett, Frank (Distributed by Warner Home Video, 2009)
Wacky romantic comedy about a woman jilted at the altar by her gadabout suitor, and the man who consoles her.